Policy Of Patent Law On Public Health And Medical Products: Discourse In Indonesia Government's Use Of Intellectual Property (Journal of Namibian Studies : History Politics Culture, 2024)
The protection of Intellectual Property Rights particularly  on Patents Policy is very important because the Intellectual Property System provides limitations on the application of Patent Invention on public health, medical and others pharmaceutical products including vaccines. Learning from the pandemic situation, national policy (especially developing countries, with in unequal positioning because of the arguments of developed countries with large industries due to the provisions of the Trade Related Aspect of Intellectual Property Rights (TRIPs) Agreement. In the other hand  Compulsory License as standard instrument that makes intellectual property exclusively but confront with International trade as a legal instrument. The research problems, about  of patent policy for pharmaceutical and vaccine products in the Intellectual Property Rights (IPR) protection System in the scope of international trade. Research results show that There is National Protection and  government’s use Exclusivity of Patent for Inventions in scope of drugs, including others medical and pharmaceutical products. In the scope of Intellectual Property System Patents Policy is an opened option that the mechanism can be applied for Public and Social Interests in the sector of national interest, security and public health. Developing countries with lack of facilities continues to fight for equal access before International Cooperation (both bilateral and multilateral) within the scope of international relations is aimed in strengthening cooperation to solve common problems.